Mandar-Culture-Based Political Education in Preventing Money Politics in the 2024 Election in Majene Regency - Handayani Razak , Fitriani Sari; Farhanuddin; Sajidin, Muhammad; Rivai, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
Low public participation in monitoring election violations will affect elections with integrity and dignity. The practice of money politics will create corruption and harm society. This research discusses the political education of the Mandar Tribe community in preventing the practice of money politics in the 2024 elections. This research uses a descriptive qualitative research method by collecting primary data through a structured questionnaire-based survey. The data collection technique uses nonprobability sampling, namely purposive sampling which is used to select respondents from the community, the KPU and Bawaslu of Majene Regency, election participants and the Majene Regency government. The research results show that society's vulnerability to money politics is quite high, so prevention is needed through political education by election management institutions, the government and political parties. The level of community political participation is quite good through comprehensive strategic approaches such as outreach from election organizers through My Ads and outreach to prevent money politics involving figures in the community with Mandar political, legal and cultural education. The conclusion of this research is that the practice of money politics can be prevented through collaborative movements involving various stakeholders, including election organizers, government, political parties and community groups.